2020
DOI: 10.1038/s41598-020-58478-6
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and post-stroke depressive symptoms

Abstract: our study aimed to explore the association between serum c-reactive protein (cRp) and post-stroke depressive symptoms. We prospectively recruited 572 patients with ischemic stroke or transient ischemic attack in whom serum CRP level was measured within 48 h after stroke onset. Depressive symptoms were assessed at day 8 and 3 months after stroke in 405 and 306 patients, respectively. Patients with greater depressive symptoms at day 8 and patients with greater depressive symptoms 3 months after stroke had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Patients from Group 2 (D+/D −) were also more likely to have history of stroke or TIA compared with other groups. Our previous study showed that a history of stroke is a predictor of early, but not late post-stroke depressive symptoms (Kowalska et al 2020 ). In contrast, Eriksson et al found an association between a history of stroke and self-reported depression 3 months after stroke (Eriksson et al 2004 ).…”
Section: Discussionmentioning
confidence: 97%
“…Patients from Group 2 (D+/D −) were also more likely to have history of stroke or TIA compared with other groups. Our previous study showed that a history of stroke is a predictor of early, but not late post-stroke depressive symptoms (Kowalska et al 2020 ). In contrast, Eriksson et al found an association between a history of stroke and self-reported depression 3 months after stroke (Eriksson et al 2004 ).…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have examined the relationship between circulating CRP and risk of post-stroke depression with conflicting results [ 42 , 43 , 44 ]. In the previous sub-study, we found that this association was significant for depression diagnosed during hospitalization, but there was no association between depression diagnosed three months post-stroke and CRP levels [ 45 ]. Interestingly, in this present, much larger study, patients with depression, diagnosed at the hospital, had significantly higher level of CRP than dementia-free patients, thus supporting the hypothesis of the role of immunological mechanisms in development of depressive symptoms.…”
Section: Discussionmentioning
confidence: 98%
“… 42 Kowalska et al found that higher levels of CRP are associated with greater depressive symptoms after stroke. 43 A meta-analysis of previous prospective and retrospective studies showed that higher level of CRP in the acute phase of stroke suggested an increased risk for PSD. 11 Inflammation is conducive to dysfunction of synaptic plasticity and ultimately depression by mediating alterations in neurotransmitters, particularly the synthesis and metabolism of 5-hydroxytryptamine and glutamine.…”
Section: Discussionmentioning
confidence: 99%